THE IMPORTANCE OF ENGLISH WRITING SKILLS IN SOCIAL MEDIA USAGE FOR GENERATION Z AT IAIN KERINCI - Suhaimi; Saputra, Aulia Rachmad Pidie (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
In the digital age, social media has become a very important communication platform, especially for Generation Z. This study explores the importance of writing skills in English in the use of social media among IAIN Kerinci students. Using a qualitative phenomenological approach, data was collected through interviews with eight students majoring in English Education. The results showed that students of the English education study program argued that writing skills in English play a significant role in effective communication, self-image building, and career opportunities. Students feel that writing in English enhances their credibility and expands their professional network. However, there are various challenges that hinder the development of their writing skills, such as fear of grammatical errors, lack of confidence, and minimal exposure to English content. This study highlights the need for institutional support to improve students' writing skills through structured learning strategies and social encouragement. The findings contribute to the understanding of the relationship between digital literacy and language skills in both academic and professional contexts.